Checklist of polychaetous annelids in Malaysia with redescription of two commercially exploited species - Idris, Izwandy; Arshad, Aziz (Academic Journals, 2013)
A checklist of polychaetous annelids identified within Malaysian territory is presented. The checklist is produced based on the collected specimens by the present authors and from published materials. Two species from the checklist that are currently commercially exploited were described in detail based on their original descriptions as well as current observation. In total, 64 polychaete species from 31 families have been identified in Malaysia from 1866 until present. The two described species, Halla okudai Imajima, 1967 and Diopatra claperedii Grube, 1878 are harvested as baitworms along the west coast of Peninsular Malaysia. The checklist has extended the distribution of these two species from their previous records. The number of polychaete species identified in Malaysia is lower than its neighbouring countries except the Philippines. The polychaete research in Malaysia is evaluated and research direction is commented.